Light-Dependent Biosynthesis of Silver Nanoparticles Mediated by Microalgal Cell Extract - Bao, Zeqing (Université d'Ottawa / University of Ottawa, 2018)
Silver nanoparticles (AgNPs) are a promising nanomaterial with numerous applications and high level of commercialization. Biomass-mediated AgNP synthesis has emerged as a novel approach for producing AgNPs and microalgal biomasses have been found particularly advantageous. However, few studies have so far focused on microalgae-mediated biosynthesis and the mechanism of AgNP biosynthesis is still elusive. The purpose of this study was twofold: 1) to investigate effects of different parameters on the biosynthesis of AgNPs; 2) to investigate the mechanisms involved in such a bioprocess. It was found that the cell extract of Neochloris oleoabundans prepared by whole cell aqueous extraction (WCAE) in boiling water bath was able to reduce Ag+ to AgNPs. It was further discovered that sonication of algal cells before extraction could enhance the efficiency of cell extraction and enable AgNP biosynthesis using cell extract obtained by disrupted cell aqueous extraction (DCAE) at room temperature. Light was required for AgNP biosynthesis and rainbow tests showed that purple and blue lights were particularly necessary. Based on experimental results, we hypothesize the mechanism of microalgae-mediated AgNP synthesis to be a chlorophyll-mediated reaction, in which chlorophylls are excited upon absorbing photons in the purple and blue spectra and donate electrons to reduce Ag+, the lost electrons are replenished by water-splitting reaction.
Keywords: Silver nanoparticles; Microalgae; Biosynthesis; Chlorophyll; Light-dependent reaction; Mechanism